Maternal Anxiety Symptoms and Chinese Adolescents' Mental Health During the COVID-19 Pandemic: The Protective Role of Adolescents' Self-Compassion - Zhou, Tong; Bian, Xiaohua; Zhang, Kening; Zheng, Shanyun; Lin, Yinuo; Zheng, Hong; Liu, Junsheng; Finan, Julia (Frontiers in Psychiatry, 2022)
The COVID-19 outbreak triggered dramatic changes to family life. Parents, especially mothers, were found to experience more psychological distress during the pandemic, which may have had an impact on their children’s mental health. The primary goal of this study was to examine the potential protective role of adolescents’ self-compassion in the relationship between maternal anxiety and adolescents’ mental health during the COVID-19 pandemic. Participants included 5,720 adolescents (48.9% girls; Mage=11.60, SDage = 1.36) and their mothers from Zhengzhou city, Henan province in Mainland China. Adolescents reported their level of self-compassion, PTSD symptoms, and negative affect during the COVID-19 pandemic. Mothers reported their own anxiety symptoms and their children’s depression and anxiety symptoms. Results indicated that older female adolescents reported higher levels of PTSD symptoms and negative affect, and lower levels of self-compassion than their counterparts. Maternal anxiety during the COVID-19 pandemic was consistently positively associated with adolescents’ psychological maladjustment. These associations were buffered by adolescents’ self-compassion. Specifically, adolescents with higher levels of self-compassion were found to be less psychologically affected by their mothers’ anxiety during the COVID-19 pandemic. Findings highlighted the possibility of improving adolescents’ mental health through fostering their self-compassion during the COVID-19 pandemic.